Slayers, rippers, and blitzes: dark humor and the justification of cruelty to possums in online media in New Zealand - Major, Emily (Frontiers in Communication, 2024)
The representation of ‘pest’ animals in mass media can reflect wider societal attitudes about belonging, race, and purity. In New Zealand, the Australian brushtail possum (Trichosurus vulpecula) is portrayed as the nation’s top enemy. This project examined online news articles published in New Zealand between 2016 and 2023 to explore how possums were framed after the creation of the Predator Free 2050 ‘pest’ eradication campaign that sought to eradicate all invasive rats, stoats, and possums. Through a process of qualitative thematic analysis, it was discovered that themes of militancy, economy, and desensitization of cruelty were paired with dark humor and extreme objectification of possums. This has created a culture of creaturely racism and speciesist xenophobia that presents cruelty as patriotism. A new media ethics that prioritizes an intersectional, anti-speciesist praxis is necessary to prevent the nation’s enculturation of vigilante slayers who are encouraged to kill those deemed to not belong.